When Sustainability Talks but Profits Decide: Evidence from Corporate Tax Payments - Linda Ayu Wulandari; Hendro Paulus (Jurnal Dinamika Akuntansi, 2026)
Purposes: This research is conducted to examine as how the sustainability signal represented by En- vironmental, Social, Governance Disclosure as an internal sustainability narrative and PROPER rat- ing as an external verified sustainability signal, there is also financial pressure and growth pressure will affect the corporate tax payment whether the condition of profitability is forcing the company. Methods: This research will conduct with Moderated Regression Analysis of panel data from 135 observations basic material entities achieving PROPER on 2020-2024 by Ministry of Environment and Forestry of Indonesia Republic with the tools to examine is EViews 13. Findings: The results indicate that ESG disclosure has a significant negative effect on corporate tax payment, suggesting that internal sustainability narratives may remain symbolic without sufficient economic capacity. In contrast, PROPER ratings positively influence tax payment, reflecting the role of externally verified sustainability signals in strengthening fiscal compliance. Financial pressure increases tax payments through creditor monitoring, while growth pressure reduces tax payments as firms prioritize internal funding for expansion. Profitability acts as a forcing condition, strength- ening the ESG effect, weakening the influence of PROPER and financial pressure, and offsetting the negative impact of growth pressure on corporate tax payment. Novelty: This study reframes sustainability disclosure as a sustainability signal rather than a direct de- terminant of tax behavior and conceptualizes corporate tax payments as observable fiscal outcomes. By positioning profitability as a forcing condition, this study offers a mechanism base explanation of how sustainability and economic pressures interact in environmentally regulated industries.